Defining Authenticity of the Y Balance Test Implemented by an Intellectual Programmed Tool in Inclusive Physical Education - Blavt, Oksana; Zahura, Fedir; Helzhynska, Tetiana; Khimenes, Khrystyna; Huska, Mykhailo; Gurtova, Tetyana; Levandowska Lіubov; Tymkovych, Rostyslav (Physical Education Theory and Methodology, 2025)
Objectives. The study aimed to investigate the authenticity of the Y Balance Test for the lower quarter (LQYBT), implemented by a developed intelligent programmable tool for students after blast TBI with acoustic trauma. Materials and methods. At the theoretical level, analysis, synthesis, systematization, and generalization were used, while at the empirical level, technical modeling, applied programming, a pedagogical experiment using the LQYBT, and mathematical statistics were employed. The study sample consisted of first-year students after mild blast TBI with acoustic trauma. Results. The results are presented in a developed intelligent programmable tool for LQYBT implementation. The development of the tool involved using the MPU-6050 GY-521 module, which is placed into the sole of the footwear intended to perform LQYBT. Another element of the developed tool is “intelligent vectors”, which are placed on the axes of LQYBT execution and consist of a matrix of pressure sensors. This matrix registers pressure changes at the points of contact for the student’s foot and automatically identifies loss of balance, foot movement, or errors related to changes in body position. Integrating information from the MPU-6050 GY-521 module and “intelligent vectors” is facilitated by using the Arduino Uno board comprising the ATmega328P microcontroller as the main processor and the ATmega16U2 microcontroller for communication with a PC via a USB port. The board recognizes signals and transmits them sequentially to a PC, where they are processed by the developed software and displayed on the screen. Wireless infrared communication is used to transmit the signal. A key feature of this smart tool is the use of artificial intelligence. The reliability and validity indicators of LQYBT after blast TBI with acoustic trauma, when the results are recorded by the teacher, correspond to the “average” and “acceptable” levels. When using the developed tool, they reached the “high” level. Conclusions. The findings suggest that using an intelligent programmable tool for the implementation of LQYBT is a powerful means of monitoring the current state of balance in students after blast TBI with acoustic trauma in real time, its permanent analysis and forecasting, for making timely and adequate management decisions regarding the rehabilitation program in the process of inclusive physical education.